Tampilan Reproduksi Kambing Lokal Yang Mengalami Kombinasi Sinkronisasi Berahi Dengan Prostaglandin F2-Alfa dan KEhadiran Pejantan - Tongku Nizwan Siregar (Jurnal Agripet, 2001)
ABSTRACT.The objective of this study is to know the effectivity of oestrus syncronizination and male effect combination in local does. A research was carried out of ten healthy female local does, 2.5-3.5 years old and non in oestrus or gravid condition. Does are divided in to groups, which consist of 5 does. Oestrus was synchronize by intramuscular injection of 125 u cloprostenol (estroplan TM). The does were injected twice at on interval of 10 days. After second group introduce with one male while at first group without male ever. The second injection was accoplished after the does revealed the charactristic oestrus sign alliwed mating naturally. The percentage of does revealed oestrus after synchronize and male effect combination process (100% vs 100%) with onset of oestrus showed not significantly difference (38.4 9.37 vs 34.4 9.53). All female does were become gravid(100% vs 100%)with average of number of kids was notsignificantly (1.2 0.45 vs 1.8 0.45).